The IRP/IRE system in vivo: insights from mouse models - Wilkinson, Nicole; Pantopoulos, Kostas (Frontiers in Pharmacology, 2014)
Iron regulatory proteins 1 and 2 (IRP1 and IRP2) post-transcriptionally control the expression of several mRNAs encoding proteins of iron, oxygen and energy metabolism. The mechanism involves their binding to iron responsive elements (IREs) in the untranslated regions of target mRNAs, thereby controlling mRNA translation or stability. Whereas IRP2 functions solely as an RNA-binding protein, IRP1 operates as either an RNA-binding protein or a cytosolic aconitase. Early experiments in cultured cells established a crucial role of IRPs in regulation of cellular iron metabolism. More recently, studies in mouse models with global or localized Irp1 and/or Irp2 deficiencies uncovered new physiological functions of IRPs in the context of systemic iron homeostasis. Thus, IRP1 emerged as a key regulator of erythropoiesis and iron absorption by controlling hypoxia inducible factor 2α (HIF2α) mRNA translation, while IRP2 appears to dominate the control of iron uptake and heme biosynthesis in erythroid progenitor cells by regulating the expression of transferrin receptor 1 (TfR1) and 5-aminolevulinic acid synthase 2 (ALAS2) mRNAs, respectively. Targeted disruption of either Irp1 or Irp2 in mice is associated with distinct phenotypic abnormalities. Thus, Irp1-/- mice develop polycythemia and pulmonary hypertension, while Irp2-/- mice present with microcytic anemia, iron overload in the intestine and the liver, and neurologic defects. Combined disruption of both Irp1 and Irp2 is incombatible with life and leads to early embryonic lethality. Mice with intestinal- or liver-specific disruption of both Irps are viable at birth but die later on due to malabsorption or liver failure, respectively. Adult mice lacking both Irps in the intestine exhibit a profound defect in dietary iron absorption due to a “mucosal block” that is caused by the de-repression of ferritin mRNA translation. Herein, we discuss the physiological function of the IRE/IRP regulatory system.